From idea to impact: reviewing innovation perspectives of creators and consumers in the foodservice sector / Esther Sii Wei Ling, Bee-Lia Chua and Wan Melissa Wan Hassan - Ling, Esther Sii Wei; Chua, Bee-Lia; Wan Hassan, Wan Melissa (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2023)
The foodservice industry is in a constant state of evolution, driven by the necessity for innovation to remain competitive. In this study, firm and consumer perspectives on innovation in the foodservice industry are examined. A comprehensive literature review of innovation in the foodservice industry is conducted, highlighting the different perspectives innovation can take, such as firm innovation, consumer innovativeness, and customer perceived innovativeness. Innovation is a complex concept that necessitates a holistic understanding and measurement of each perspective, as well as the consideration and collaboration of multiple perspectives when analysing innovation. Overall, the review finds that successful innovation in the foodservice industry requires a deep understanding of the needs and preferences of consumers. By focusing on the journey from idea to impact, the review provides valuable insights into how innovation can drive growth and success in the foodservice sector.